POTENTIAL ANTIFUNGAL ACTIVITY OF DIFFERENT HONEY BRANDS FROM PAKISTAN: A QUEST FOR NATURAL REMEDY - Ahmad, Kafeel; Khalil, Ali Talha; Somayya, Ramla; Khan, Faisal Nouroz; Shah, Ali Raza; Ovais, Muhammad; Shinwari, Zabta Khan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Besides a wholesome food, honey is known for its therapeutic implications. We investigated the antifungalactivity of five honeys of different types from Pakistan against various pathogenic fungal strains. Antifungal properties ofprocessed and non-processed honey were determined.Materials and Methods: The antifungal assay of honey was carried out against Aspergillus niger, Aspergillus flavus,Aspergillus fumigates, Alterneria alternata, Fusarium solanai, Microsporum canis, Penicillium funiculosium and Rhizopussolanai. Different dilutions of honey samples were used (20%, 50%, 70%, 90% and 100% w/v so as to find out theminimum effective concentration of each honey type.Results: It was observed that all of the honey samples were highly active, with percent inhibition range of (3-81%) forAspergillus niger, (2-82%) for Aspergillus flavus, (1-76%) for Aspergillus fumigates, (1-84%) for Alterneria alternata, (2-67%) for Fusarium solanai, (1-87%) Microsporum canis, (2-78%) Penicillium funiculosium and (1-86%) for Rhizopussolanai.Conclusion: The study of Pakistani honey brands reveals that they possess a substantial antifungal nature. Therefore, theymay be used in curing fungal infections along with antifungal drugs as a cheaper alternative natural remedy with no sideeffects.